Transformasi Sosial-Politik Dakwah Nabi Muhammad: Analisis Sosio-Historis Mekah-Madinah - Andi Alif Afwan; Amrudin; Susmihara; Syamzan Syukur (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Studies on the Prophet Muhammad’s da‘wah commonly approach the Meccan–Medinan period through normative-theological perspectives or descriptive historical narratives, leaving the socio-political dimension of transformation and its relevance to contemporary leadership insufficiently explored. This article aims to analyze the transformation of the Prophet Muhammad’s da‘wah from Mecca to Medina as a process of socio-political change using a socio-historical approach. This study employs qualitative library research, drawing on primary sources such as the Qur’an, hadith, and classical sirah literature, as well as secondary sources from contemporary scholarly works. Data are analyzed descriptively and analytically by reconstructing historical contexts and examining shifts in social structures, power relations, and prevailing values in Meccan and Medinan society.The findings reveal that the Meccan da‘wah functioned as a moral and social transformation movement that challenged tribalism, social inequality, and the legitimacy of the Quraysh elite, while simultaneously laying the ideological foundation of the early Muslim community. This transformation reached its institutional form in Medina through the formation of a plural and organized political community, as reflected in the Charter of Medina. The study argues that the success of the Prophet’s da‘wah was not solely religious but also socio-political, embodied in a model of prophetic leadership grounded in moral exemplarity, consultation (shura), justice, and social compassion. This article contributes to socio-political Islamic studies by offering a socio-historical interpretation of prophetic da‘wah and highlighting its relevance for contemporary leadership and governance.